Handbuch Inklusion international / International Handbook of Inclusive Education Globale, nationale und lokale Perspektiven auf Inklusive Bildung / Global, National and Local Perspectives - Köpfer, Andreas; Powell, Justin JW; Zahnd, Raphael (Verlag Barbara Budrich, 2021)
Global paradigm, national norms and local practices. The International Handbook of Inclusive Education combines theoretical approaches and myriad comparative perspectives on inclusive education considering its global diffusion. Its contributions provide comprehensive access to international discourses, comparative research results, and inspiring practices from diverse world regions-Europe, Africa, Asia, and North America-and emphasize the relevance of comparative studies.